Student expectations on sports festivals with a view to the estimation questionnaire on Campus Sports Festival - Fenyves, Veronika; Becsky, András; Dékán, Tamás; Nyul, Balázs (Applied Studies in Agribusiness and Commerce, 2015)
Campus Festival, organized each year, is listed as one amongst the music festivals in Hungary attracting crowds, with a target audience formed by higher education students. The organizers of Campus Festival set as their main highlighted objective, in addition to providing with musical events, the enhancement of the sporting life of the visitors stopping by. As a side event, Campus Sports Festival is launched each time along with it, with the intention to promote sports and doing sports, creating an event for the public suitable for the development of crossborder student relationships, between fans and contenders. This study is to demonstrate student expectations with a view to the questionnarebased needs assessment prepared on sports festivals.